General PMSM d,q-Model Using Optimized Interpolated Absolute and Differential Inductance Surfaces - Piepenbreier, Bernhard; et al. (International Electric Machines and Drives Conference 2011 (IEMDC 2011), 2011)
Widely used permanent magnet synchronous machines (PMSMs) often show a significant inductance variation near and above the rated current values due to saturation. When the inductances are no longer constant, the model equations have to be modified. This paper proposes new, extended equations, which are as similar as possible to the linearized equations, to make the conversion of existing control schemes to the new approach as easy as possible. In addition, methods to measure the inductances needed for the new PMSM equations are explained together with an efficient implementation of the inductances. © 2011 IEEE.
UnivIS-Import:2015-04-16:Pub.2011.tech.IE.LEEAS.genera